Biometric technology in banking institutions: ‘The customers’ perspectives’ - Abraham Morake; Lucas T. Khoza; Tebogo Bokaba (South African Journal of Information Management, 2021)
Background: Over the years, attention has been focused on digital banking and financial technology with little or no attention being paid to biometric banking technology.